2010
DOI: 10.1111/j.1600-051x.2010.01572.x
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal infection and subclinical atherosclerosis: the role of high‐density lipoprotein as a modifying factor

Abstract: HDL levels or factors closely associated with HDL levels appear to modify the association between periodontal infection and certain parameters of subclinical atherosclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 19 publications
1
6
0
2
Order By: Relevance
“…To date, using these data, we have not studied whether subjects with simultaneous severe periodontal infection and unfavourable lipid composition are truly at higher risk of cardiovascular disease compared with subjects with the single risk of periodontal infection or unfavourable lipid composition. At present, there is little to support such an interpretation, but the results of this study, which would seem to be a fairly new finding, are in agreement with the finding of our earlier study in which we reported that periodontal infection was associated with atheroma formation among subjects with low HDL (Ylo¨stalo et al 2010). Whether it is the case of a true interaction remains to be confirmed in future studies.…”
Section: Implications Of the Studysupporting
confidence: 89%
“…To date, using these data, we have not studied whether subjects with simultaneous severe periodontal infection and unfavourable lipid composition are truly at higher risk of cardiovascular disease compared with subjects with the single risk of periodontal infection or unfavourable lipid composition. At present, there is little to support such an interpretation, but the results of this study, which would seem to be a fairly new finding, are in agreement with the finding of our earlier study in which we reported that periodontal infection was associated with atheroma formation among subjects with low HDL (Ylo¨stalo et al 2010). Whether it is the case of a true interaction remains to be confirmed in future studies.…”
Section: Implications Of the Studysupporting
confidence: 89%
“…Considerations should also be given when the positive correlations between OB, BMI and HDL in the CP group take into account. As known, hs-CRP and blood lipid levels were suggested to be important markers to have a role in the relationship between periodontal disease and the systemic diseases [50][51][52]. Accordingly, this result, when related to the systemic effect of the chronic local inflammation, may explain the relationship (directional or bi-directional) between the periodontal and systemic diseases when the systemic effects of adipokines (cardiovascular, obesity and diabetes mellitus [53]) are considered.…”
Section: Discussionmentioning
confidence: 88%
“…Recent studies indicated that periodontitis may be a risk factor for worsening glycemic control, impairing endothelial function among patients with diabetes, and also may increase the risk of cardiovascular events, such as myocardial infarction and stroke. hsCRP and HDL are two risk markers for cardiovascular disease (28,29). And an epidemiological extrapolation from the UK Prospective Diabetes Study (UKPDS) predicts that for every 1% reduction in HbA1c there would be an associated 21% reduction in risk for any diabetes-related endpoints, including both microvascular (37% reduced risk of microvascular complications) and macrovascular (14% reduced risk of myocardial infarction) complications (30).…”
Section: Discussionmentioning
confidence: 99%